Continuous reaction monitoring by dielectric spectroscopy - Dalligos, Desiree (2024)
Off-line monitoring is a valuable method in research and industrial processes for obtaining important information of a process or chemical reaction. Unfortunately, it is time consuming, inefficient and challenging for reactions that use toxic reagents and high temperature/ pressure conditions. Furthermore, this method consists of safety hazards to the operators. An alternative approach is to continuously monitor the reaction in situ by employing the appropriate process analytical technique. There are many analytical techniques available, however, there is no single analytical technique that can be applied to every system.